Crédito fundiário: uma política de reforma da estrutura agrária ou de acesso à terra para ampliar a área dos pequenos proprietários? - Pelegrini, Gelson (2018)
The Brazilian landholding is an issue not solved yet. The owning of the land is centered, what blocks the access by several farmers with few or no land. The Agrarian Credit (AC) is a public policy that, by financing, intends to improve the access to land by family farmers, which are owners of smallholdings, and for famers with poor or no access to land, such as partners, leaseholders, aggregates, and squatters. In Brazil, the AC was created in the end of the 90s, by a cooperation between the Brazilian Government, and the World Bank, with the objective of improving the land market and fighting against the rural poverty. The AC contributes to the land hold restructuring by the access to land by farmers who expand their properties, or buy new land areas. In the Territory of the Middle High Uruguay Citizenship more than 10% of the production unites was benefited by AC, what provides elements that can contribute in the evaluation of the importance of this public policy in the local and national landholding issue. This study uses the theoretical and methodological reference of the analysis and diagnosis of the agrarian systems to understand the process of access to land, through AC, in Frederico Westphalen, RS. The farming trend in the town led to the definition of three different farming zones: the capitalized, the decapitalized and the one in process of capitalization. The farmers are distributed in equitable numbers in the zones, although the economic and productive matrixes are maintained. In other words, the AC does not contribute to the changing of the local farming. From 2000 to 2014, 163 farmers used AC in the town, 12 of them were rural workers, 32 were farmers with poor access to land, 37 owners, and 82 were farmers’ children. Among these categories, respectively 16,3%, 37,5%, 75,7%, and 72% of the farmers kept on working on the properties they bought. 64 of the beneficiaries of the AC created a new Family Production Unit (FPU), and 99 of them added new land to the existing. Respectively, 43,7% and 73,3% of the farmers still keep working on farming. By the analysis of the types of the production systems, it was verified that the AC brings better results to the families of farmers which own a smallholding, since it has a productive structure, and the production systems, mostly, need the enlargement of the land area to feasible the farming profit to the family. As it was implemented, the AC policy has difficulties on encouraging the creation of new family production units, mainly in order to make feasible the productive structure and the acquisition of a minimum useful area to obtain the farming income necessary to achieve the level of social reproduction and the payment of credit installments.